2008
DOI: 10.1523/jneurosci.4498-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in aDrosophilaα2δ Voltage-Gated Calcium Channel Subunit Reveal a Crucial Synaptic Function

Abstract: Voltage-dependent calcium channels regulate many aspects of neuronal biology, including synaptic transmission. In addition to their ␣ 1 subunit, which encodes the essential voltage gate and selective pore, calcium channels also contain auxiliary ␣ 2 ␦, ␤, and ␥ subunits. Despite progress in understanding the biophysical properties of calcium channels, the in vivo functions of these auxiliary subunits remain unclear. We have isolated mutations in the gene encoding an ␣ 2 ␦ calcium channel subunit (d␣ 2 ␦-3) usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 61 publications
8
92
0
Order By: Relevance
“…A gene incorrectly termed CACNA2D5 in an article by Whittaker and Hynes (2002) has the sequence of a 2 d-4 (CACNA2D4), and the more remotely related gene, erroneously termed CACNA2D4 in that review corresponds to the more distantly related CACHD1, and has not yet been characterized. Homologous genes are also found in Drosophila melanogaster and Caenorhabditis elegans (Dickman et al, 2008;Saheki and Bargmann, 2009) and have been characterized to affect both calcium channel and presynaptic functions. Furthermore, proteins of the CLCA gene family, which have a related domain structure, have been identified to be auxiliary subunits of calcium-activated chloride channels (Yurtsever et al, 2012).…”
Section: A a 2 D Subunit Genes And Gene Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…A gene incorrectly termed CACNA2D5 in an article by Whittaker and Hynes (2002) has the sequence of a 2 d-4 (CACNA2D4), and the more remotely related gene, erroneously termed CACNA2D4 in that review corresponds to the more distantly related CACHD1, and has not yet been characterized. Homologous genes are also found in Drosophila melanogaster and Caenorhabditis elegans (Dickman et al, 2008;Saheki and Bargmann, 2009) and have been characterized to affect both calcium channel and presynaptic functions. Furthermore, proteins of the CLCA gene family, which have a related domain structure, have been identified to be auxiliary subunits of calcium-activated chloride channels (Yurtsever et al, 2012).…”
Section: A a 2 D Subunit Genes And Gene Productsmentioning
confidence: 99%
“…The a 2 d subunits have a similar domain structure to many proteins involved in extracellular matrix and extracellular protein-protein interactions (Whittaker and Hynes, 2002). Indeed, a 2 d-1 has been reported to interact with thrombospondins and to have a structural role in synapse formation (Eroglu et al, 2009), and the a 2 d proteins in Drosophila have been shown to have an effect on presynaptic morphology (Dickman et al, 2008;Kurshan et al, 2009), as is also the case for a 2 d-3 in an auditory system synapse (Pirone et al, 2014). Since a 2 d subunits are involved in calcium channel trafficking as well as function, it may be difficult to tease apart their roles independent of calcium channels.…”
Section: A a 2 D Subunit Genes And Gene Productsmentioning
confidence: 99%
“…These proteins, ACYPI005770 and ACYPI008838, show 71% and 47% similarity to the D. melanogaster orthologue, respectively. D. melanogaster also has three a2d subunits, which are post-translationally cleaved into two peptides (a2 and d) (Dickman et al, 2008), and the analysis of the A. pisum genome reveals four orthologues of these genes with the a2d 1 subunit being duplicated (Supplementary Table S2). …”
Section: Sodium Channel 60ementioning
confidence: 99%
“…Knockdown of Ca 2+ channels by RNA interference yields reduced nerve-terminal growth (Rieckhof et al, 2003). Conversely, loss-of-function mutations in the  2  voltage-gated Ca 2+ -channel subunit cause enhanced nerve-terminal growth (Dickman et al, 2008;Ly et al, 2008). However, nerve-terminal growth was not altered in fuseless mutants, which probably have defects in intraterminal Ca 2+ levels, because defects in  1 -subunit trafficking were reported (Long et al, 2008).…”
Section: Frq Negatively Regulates Nerve-terminal Growthmentioning
confidence: 99%